(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This study examines the biophysical properties of blood and their alterations in cardiovascular diseases. Blood rheology, which involves the viscosity, elasticity, and flow characteristics of blood, plays a crucial role in maintaining normal cardiovascular function. In cardiovascular diseases, changes such as reduced deformability of red blood cells, increased plasma viscosity, and altered blood composition lead to impaired blood flow. The research employs modern biophysical methods to assess these changes and discusses their significance in diagnosis and treatment. Therapeutic approaches aimed at improving blood rheology can help prevent complications and enhance the quality of life for patients with cardiovascular disorders.